Short- and Long-Term Efficacy of Modafinil at Improving Quality of Life in Stroke Survivors: A Post Hoc Sub Study of the Modafinil in Debilitating Fatigue After Stroke Trial - Lillicrap, Thomas P.; Levi, Christopher R.; Holliday, Elizabeth; Parsons, Mark William; Bivard, Andrew (Frontiers in Neurology, 2018)
Background The phase-II MIDAS (modafinil in debilitating fatigue after stroke) trial demonstrated that modafinil improves fatigue and quality of life in severely fatigued stroke survivors. For this study, we sought to examine the interaction between fatigue and quality of life after stroke and determine whether reducing fatigue resulted in improved quality of life. Additionally, we followed up a subset of patients 12-months after the trial to assess the long-term outcomes of modafinil therapy. Methods We used linear regression to analyse interaction between baseline fatigue, as measured by the multi-dimensional fatigue inventory (MFI), and quality of life, as measured by the stroke-specific quality of life scale (SSQoL); and between changes in MFI and SSQoL during treatment. Patients also took part in semi-structured interviews and study assessments 12-months after trial completion to assess long-term patterns of modafinil use, safety and efficacy. Results MFI and SSQoL were significantly correlated at baseline (β=-1.975 95% CI -3.082, -0.869 p<0.001), as were changes in MFI and SSQoL during treatment (β=-1.054 95%CI -1.556, -0.553, p<0.001). 18 patients agreed to 12-month follow-up, of whom 5 had continued to use modafinil. Patients taking modafinil daily demonstrated sustained improvement of 33-38 points in MFI compared to baseline. Two adverse events were reported and there was no evidence of drug tolerance. Conclusions Modafinil appears to be safe and, for at least some patients, effective long-term in fatigued stroke survivors. Alleviating fatigue has a significant relationship with improved quality of life. Clinical trial registration-URL: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=368268. Unique-Identifier: ACTRN12615000350527.